Comparative Analysis of Conservative Treatment versus Titanium Elastic Nailing in Pediatric Diaphyseal Radius and Ulna Fractures - Vidhyadhar Wadkar; PN Kulkarni (Journal of Neonatal Surgery, 2024)
Pediatric diaphyseal fractures of the radius and ulna are common and typically treated through conservative methods, such as closed reduction and casting. However, operative methods, particularly the Titanium Elastic Nailing System (TENS), have gained popularity due to their ability to provide stable fixation and facilitate early mobilization. This study aimed to compare the clinical outcomes of conservative treatment versus TENS in pediatric patients with diaphyseal radius and ulna fractures. A prospective design was used, with 100 patients divided into two groups: 50 receiving conservative treatment and 50 treated with TENS. Outcome measures included fracture union time, range of motion (ROM), complication rates, and patient satisfaction. The results showed that the TENS group had a significantly shorter fracture union time (mean 6.8 weeks) compared to the conservative group (mean 10.5 weeks). Additionally, ROM recovery was faster in the TENS group (5.5 weeks) versus the conservative group (9.2 weeks). The TENS group also experienced a lower complication rate (6%) compared to the conservative group (20%). Patient satisfaction was higher in the TENS group, likely due to quicker recovery and reduced complications. These findings indicate that TENS offers superior outcomes in terms of fracture healing, functional recovery, and patient satisfaction, especially for displaced fractures. The study suggests that TENS should be considered for pediatric forearm fractures requiring stable alignment and early mobilization, while conservative treatment remains effective for simple fractures.